Extraosseous osteoblastoma: A rare cause of breast mass in a prepubertal girl. Issue 5 (31st March 2021) - Danzinger, Sabine; Kager, Leo; Bernathova, Maria; Lang, Susanna; Haslik, Werner; Singer, Christian F.
Abstract: Extraosseous osteoblastoma of the breast, a rare disease, was diagnosed in a prepubertal girl. After tumor excision, the patient recovered well and an optimal cosmetic result was achieved. Interdisciplinary discussions about the case are essential. Abstract : Extraosseous osteoblastoma of the breast, a rare disease, was diagnosed in a prepubertal girl. After tumor excision, the patient recovered well and an optimal cosmetic result was achieved. Interdisciplinary discussions about the case are essential.